Investment, the cost of capital, and monetary policy in the nineties in France: a panel data investigation - Jean-Bernard Chatelain; André Tiomo (European Central Bank (ECB), 2001)
Using a large panel of 6,946 French manufacturing firms, this paper investigates the effect of monetary policy on investment from 1990 to 1999 through the cost-of-capital and the cash-flow channels. We compare several specifications of neo-classical demand for capital, taking into account transitory dynamics. The user cost of capital has a significant negative elasticity with respect to capital using traditional Within estimates, or as long as cash-flow is not added to the regression when using Generalised Method of Moments estimates. Asymmetries of effect of monetary policy are evaluated for different groups of firms which differ in terms of informational asymmetries. When dummy variables related to firms which are more sensitive to cash-flow are added in the model, the user cost elasticity is significant again
Keywords: C23; D21; D92; 330; cost of capital; generalised method of moments; Investment; monetary policy